Tuning of gain layer doping concentration and Carbon implantation effect on deep gain layer. Issue 1 (1st November 2022) - Mazza, S. M.; Gee, C.; Zhao, Y.; Padilla, R.; Ryan, E.; Tournebise, N.; Darby, B.; McKinney-Martinez, F.; Sadrozinski, H. F.-W.; Seiden, A.; Schumm, B.; Cindro, V.; et al.
Abstract : Next generation Low Gain Avalanche Diodes (LGAD) produced by Hamamatsu photonics (HPK) and Fondazione Bruno Kessler (FBK) were tested before and after irradiation with ~1MeV neutrons at the JSI facility in Ljubljana. Sensors were irradiated to a maximum 1-MeV equivalent fluence of 2.5E15 Neq /cm 2 . The sensors analysed in this paper are an improvement after the lessons learned from previous FBK and HPK productions that were already reported in precedent papers. The gain layer of HPK sensors was fine-tuned to optimize the performance before and after irradiation. FBK sensors instead combined the benefit of Carbon infusion and deep gain layer to further the radiation hardness of the sensors and reduced the bulk thickness to enhance the timing resolution. The sensor performance was measured in charge collection studies using β-particles from a 90Sr source and in capacitance-voltage scans (C-V) to determine the bias to deplete the gain layer. The collected charge and the timing resolution were measured as a function of bias voltage at -30C. Finally a correlation is shown between the bias voltage to deplete the gain layer and the bias voltage needed to reach a certain amount of gain in the sensor. HPK sensors showed a better performance before irradiation while maintaining the radiation hardness of the previous production. FBK sensors showed exceptional radiation hardness allowing a collected charge up to 10 fC and a time resolution of 40 ps at the maximum fluence.